Application of Work Discipline In The Effort To Increase Performance of Farid Kids Distributor Employees Karawang - Nurul Inayah; Aji Tuhagana; Dini Yani (Neo Journal of economy and social humanities, 2022)
This study aims to determine how work discipline can be applied to improve employee performance at Farid Kids Distributors. The method used in this study is qualitative and explained in detail through interviews with informants. From the application of work discipline to Farid Kids Distributors, there are still cases of disciplinary violations, especially in terms of punctuality, there are still many employees who are not punctual when entering work hours and lack of employee awareness to apply work discipline. Good discipline reflects the magnitude of a person's responsibility for the tasks assigned to him. This will encourage morale and the realization of company goals. To maintain and improve good discipline is quite difficult because of many factors that influence it. In this case, if further investigated the work discipline variables that affect employee performance. This means that the higher a person's work discipline, the higher the person's performance. It is recognized that there are many variables that are significantly related to employee performance, but one of the main factors affecting performance is work discipline.